(untitled) (Bioresearch Communications, 2023)
A total of 16 species of endophytic fungi were isolated from Centella asiatica plant. The fungi were Aspergillus flavus, A. fumigatus, A. niger, A. terreus, Cladosporium sp., Colletotrichum sp., Curvularia hominis, C. lunata, Curvularia sp., Fusarium falsiforme, F. phaseoli, Monodictys putridinis, Penicillium commune, Penicillium sp.1, Penicillium sp.2, Talaromyces trachyspermus. Among them all the fungal species were found in summer season and 12 species in winter season. The highest value of Shannon and Simpson diversity index was found in the root in summer season and the lowest value of Shannon and Simpson diversity index was found in the stem in winter season. Maximum species richness of endophytic fungi was recorded in leaf in Margalef‘s and Menhinick index in winter season. Minimum species richness of endophytic fungi was recorded in stem in Margalef‘s and Menhinick index during summer season. Bioresearch Commu. 9(2): 1263-1269, 2023 (July)